Lower Muscle Mass and Body Fat in Adolescent Idiopathic Scoliosis Are Associated With Abnormal Leptin Bioavailability. Issue 11 (1st June 2016) - Tam, Elisa M. S.; Liu, Zhen; Lam, Tsz-Ping; Ting, Terry; Cheung, Gordon; Ng, Bobby K. W.; Lee, Simon K. M.; Qiu, Yong; Cheng, Jack C. Y.
Abstract : Study Design: This was a case-control study. Objective: This study aimed to investigate the body composition and its correlation with leptin and soluble leptin receptor (sOB-R) levels in girls with adolescent idiopathic scoliosis (AIS) and compared with healthy controls. Summary of Background Data: Patients with AIS are associated with lower body weight, taller stature, lower body mass index (BMI), and deranged bone quality. Despite the widely reported lower BMI and body weight in girls with AIS, the body composition of these patients was not thoroughly studied with sufficient sample size. Leptin is an important factor in regulating energy and bone metabolism, and has been postulated as one of the etiologic factors of AIS. Methods: One hundred forty-eight AIS and 116 control girls aged 12 to 14 were recruited. Body composition was measured with bioelectrical impedance analysis. Caloric intake and physical activity level were assessed by food frequency and Baecke questionnaires respectively. Serum total leptin and sOB-R levels were measured with enzyme-linked immunosorbent assay, and free leptin index was calculated. Results: AIS girls had lower body weight and BMI, other anthropometric and sexual maturity parameters were comparable with controls. There were no difference in caloric intake and physical activity levels. After adjustment for physical activity level, AIS girls had lower skeletal muscle mass, lower body fat, and %body fat. Higher sOB-R and lower free leptin index were found in AIS girls after adjusted for age and body weight. Weaker correlations between serum total leptin, FLI, and body composition parameters were observed in AIS girls. Conclusion: Results suggested that the lower body weight in AIS girls was contributed by both lower skeletal muscle mass and lower body fat. Altered leptin bioavailability also exists in AIS girls and could lead to lower body weight, lower BMI, and abnormal body composition that were manifested in AIS simultaneously. Level of Evidence: 4